PENGARUH HARGA DAN PRODUK TERHADAP LOYALITAS KONSUMEN DENGAN KEPUASAN KONSUMEN SEBAGAI VARIABEL INTERVENING (Studi Kasus Pada Indomaret Menoreh Semarang) - Untung Widodo (Sekolah Tinggi Ilmu Ekonomi YPPI Rembang, 2015)
This study aimed to analyze the effect of pricing, product and customer loyalty with customer satisfaction as an intervening variable (Indomaret Menoreh case study in Semarang). The sampling method used purposive sampling technique. Determination of the number of samples using the formula Slovin (Rao, 1991), which resulted in a sample of 74 respondents.The method of analysis in this study using the validity, reliability, classic assumption test, multiple linear regression analysis, t test, F test and coefficient of determination. Results from this study is that there is a positive and significant effect on the price variable (X1) on consumer satisfaction (Z)., There is a positive and significant effect of the variable product (X2) on consumer satisfaction (Z), there is a positive and significant effect of the variable price (X1) on customer loyalty (Y), there is a positive and significant effect of the variable product (X2) on customer loyalty (Y), there is a positive and significant impact on consumer satisfaction variables (Z) on customer loyalty (Y).Keywords: Price, Product, Customer Satisfaction and Customer Loyalty